The Effects of Group Counseling to Enhance Attitudes toward Safety in Work Performance of Company Employees - Promsamlee, Kittisak; Wongtim, Sukaroon (Ratchaphruek Journal, 2021)
The purposes of this study were to 1) compare attitude toward safety on an experimental group of employees’ work performance, before and after receiving group counseling; and 2) compare attitude toward safety of the experimental group after receiving group counseling and a control group after receiving normal guideline.The samples consisted of 20 employees of one company who had the score lower than 25th percentile on an attitude test about employees’ safety in work performance. They were divided by simple random into the experimental group and the control group, with 10 subjects in each group. The experimental group received 8 sessions of the group counseling, which employed research lasted for 90 minutes, oppositely the control group received the safety guideline. The instruments were 1) the test on employees’ attitude with a reliability of .95 coefficient; 2) the group counseling program to enhance the attitude of employees’ safety; 3) the safety guideline that contains the statistics for data analysis were median, quartile deviation, Wilcox on matched pairs signed rank test and Mann-Whitney U test. The findings showed that 1) after receiving group counseling, the experimental group had their attitude higher than their pre-experiment at .05 level of statistical significance; and 2) after receiving group counseling, the experimental group had their attitude higher than of the control group with statistical significance at the .05 level.